The ways of formation Rodentis (Rodentia) helminth fauna in Azerbaijan - Q. Q. Fataliyev (Юг России: экология, развитие, 2015)
There were researched 314 animals related to 6 genious in different zones of Azerbaijan. It is defined that 6 genious helminthes parasits on Sсiurus anomalus, 2 genious helminthes parasits on Hystrix leucura, 5 on Myocastor coypus, 3 on Dryomys nitedula, 13 genious helminthes and etc. parasits on Arvikola terrestris –totally 28 helminthes. There were fully analyzed bioecological connection with different living organisms in Azerbaijan.